Inter-Ethnic Encounters Within the Family: Competing Cultural Models and Social Exchange. - Lomsky-Feder, Edna; Leibovitz, Tali (Journal of Ethnic & Migration Studies, 2010)
Inter-ethnic marriages have long aroused sociological curiosity, since they are perceived both as a central mechanism of mobility and as one of the more significant indicators of social integration in immigrant societies. However, we know very little about the dynamics and nature of the inter-ethnic encounters that take place within such families and whether or not they are a sphere in which ethnic dichotomies are softened. The aim of this article is to explore how members of multi-ethnic families manage inter-ethnic encounters in their daily lives. Research is based on 19 in-depth interviews, around the issue of child-raising, with members of Israeli-Jewish families—especially the spouses and their respective mothers—where one parent is an immigrant from the Former Soviet Union and the other is a locally born Misrachi. Our analysis shows that the multi-ethnic Jewish family is an arena of struggle between competing cultural models. In managing this cultural struggle the partners exchange various social resources (white ethnicity and cultural capital for 'proper' Judaism and locality) whose power derives from the surrounding social hierarchies. Based on the Israeli case, we suggest that macro-level inter-ethnic power relations and the social discourse that organises them trickle down and shape the nature of micro-level family interactions.